2013
DOI: 10.12776/amsc.v3i0.108
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Intermetallic Phase’s on the Fracture Surfaces in Secondary Aluminium Cast Alloy

Abstract: The contribution describes changes of the character of fracture surfaces depending on the morphology of intermetallic phases in secondary aluminium cast alloy. Morphology changes of intermetallic phases in recycled (secondary) aluminium cast alloy were depended on agehardening. For study was used age-hardening. The age hardening consist of solution treatment at temperature 515°C with holding time 4 hours, water quenching at 40°C and artificial aging by different temperature 130°C, 170°C and 210°C with differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 8 publications
(14 reference statements)
0
2
0
Order By: Relevance
“…These elements partly go into solid solution in the matrix and partly form intermetallic particles during solidification. The morphology of intermetallic and the size, volume depends on the solidification conditions and heat treatment of the alloys 12,13 .…”
Section: Introductionmentioning
confidence: 99%
“…These elements partly go into solid solution in the matrix and partly form intermetallic particles during solidification. The morphology of intermetallic and the size, volume depends on the solidification conditions and heat treatment of the alloys 12,13 .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies Ref. [8] have shown that the mechanical properties of the alloydecrease with the increase in the Fe concentration above 0.5%.T he presence of ap recipitate free zone (PFZ) as showni nF ig. 4a is due to the dissolution of secondary phases at high temperature that arises duringwelding.…”
Section: Microstructural Propertiesmentioning
confidence: 91%